2010
DOI: 10.1063/1.3485672
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor fluorescence enhancement from a photonics crystal surface

Abstract: A photonic crystal substrate exhibiting resonant enhancement of multiple fluorophores has been demonstrated. The device, fabricated uniformly from plastic materials over a ∼3×5 in.(2) surface area by nanoreplica molding, utilizes two distinct resonant modes to enhance electric field stimulation of a dye excited by a λ=632.8 nm laser (cyanine-5) and a dye excited by a λ=532 nm laser (cyanine-3). Resonant coupling of the laser excitation to the photonic crystal surface is obtained for each wavelength at a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…It is well known that plastic materials show significant autofluorescence when excited by near-UV or even visible radiation [3032], with autofluorescence increasing as the illumination source photon energy is increased. This phenomena was demonstrated clearly in a recent publication, in which a PCEF surface designed for multiple excitation wavelengths (λ = 532 - 633 nm) showed best signal-to-noise sensitivity performance for longer excitation wavelengths, however the detection limit for short excitation wavelengths was limited by substrate autofluorescence [33]. Meanwhile, a great deal of research activity is directed towards developing new plastic substrates with lower autofluorescence [3436].…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that plastic materials show significant autofluorescence when excited by near-UV or even visible radiation [3032], with autofluorescence increasing as the illumination source photon energy is increased. This phenomena was demonstrated clearly in a recent publication, in which a PCEF surface designed for multiple excitation wavelengths (λ = 532 - 633 nm) showed best signal-to-noise sensitivity performance for longer excitation wavelengths, however the detection limit for short excitation wavelengths was limited by substrate autofluorescence [33]. Meanwhile, a great deal of research activity is directed towards developing new plastic substrates with lower autofluorescence [3436].…”
Section: Introductionmentioning
confidence: 98%
“…In this work, the PC was intentionally designed to interact efficiently with a laser in the red part of the optical spectrum (λ = 637 nm), which coincides with the excitation wavelength of fluorophores for labelling cell structures. The approach described here may be extended to any other wavelength from UV 36 to IR 37 by selection of the PC period, and we have demonstrated that a single PC may be used to excite fluorophores with multiple excitation wavelengths 38 . The PCs used for all experiments reported here have a grating period of Λ = 400 nm, depth of d = 50 nm, and duty cycle of f = 50%.…”
Section: Resultsmentioning
confidence: 99%
“…The “PC enhanced extraction” effect operates independently of the PC enhanced excitation effect, and thus their contributions multiply, resulting in the ability to achieve overall PC enhanced fluorescence [6567] (PCEF) effects as high as 7500× [17, 68, 69]. PCEF has been applied to boost the signal-to-noise ratio for fluorescent dye molecules [65, 7072], quantum dots [65, 67], and Raman scattering [7375] for applications in biosensing and high efficiency lighting [76, 77].…”
Section: Introductionmentioning
confidence: 99%